Report of the General Education Task Force - Kansas State University, K-State First (Kansas State University. K-State First., 2007)
A report regarding the Kansas State University's General Education Task Force's experience of the 2006-2007 school year. Included in the report is a summary of recommendations, an outline of the task force and its work, detailed recommendations for a General Education Plan, recommendations regarding implementation, and sources used in creating the report.
Keywords: First-year experience program; Education general; Reports; Papers (document genres)